2003
DOI: 10.1515/znc-2003-5-603
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils of Two Chinese Endemic Meconopsis Species

Abstract: The essential oils from two Chinese endemic Meconopsis species, i. e., M. punicea and M. delavayi, were analyzed by using GC-MS for the first time. The major constituents were hexadecanoic acid (16.8%), 1,2-dimethyl naphthalene (11.4%), 1,4-dimethyl naphthalene (6.6%), 1,3-dimethyl-5-ethyl naphthalene (5.9%), and 3-methyl biphenyl (5.6%) for M. punicea, and hexadecanoic acid (9.9%), 1,2-dimethyl naphthalene (7.9%), 1,3-dimethyl-5-ethyl naphthalene (6.2%), tetradecane (5.9%), and hexyl cinnamaldehyde (5.5%) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Franch. Ex Prain (Slavík and Slavíková;Yuan et al, 2003); and santolina alcohol was reported from plant Achillea filipendulina Lam. (Sharopov and Setzer, 2010).…”
Section: Slmentioning
confidence: 99%
See 1 more Smart Citation
“…Franch. Ex Prain (Slavík and Slavíková;Yuan et al, 2003); and santolina alcohol was reported from plant Achillea filipendulina Lam. (Sharopov and Setzer, 2010).…”
Section: Slmentioning
confidence: 99%
“…No. As a traditional medicinal plant for antiinflammatory and analgesic activity Yuan et al (2003) 28 1H-3a,7-methanoazulene, 2,3,4,7,8,8a-hexahydro-3,6,8,8tetramethyl-, [3R-(3à,3aá,7á,8aà) bioactive (volatile and nonvolatile) compounds. A summary of the pharmacological studies with the metabolites detected in the present study is given in Table 9.…”
Section: Slmentioning
confidence: 99%